Galactic fountains and the rotation of disc-galaxy coronae - Marinacci, F; Fraternali, F; Nipoti, C; Binney, J; Ciotti, L; Londrillo, P (2011)
In galaxies like the Milky Way, cold (~ 10^4 K) gas ejected from the disc by stellar activity (the so-called galactic-fountain gas) is expected to interact with the virial-temperature (~ 10^6 K) gas of the corona. The associated transfer of momentum between cold and hot gas has important consequences for the dynamics of both gas phases. We quantify the effects of such an interaction using hydrodynamical simulations of cold clouds travelling through a hot medium at different relative velocities. Our main finding is that there is a velocity threshold between clouds and corona, of about 75 km/s, below which the hot gas ceases to absorb momentum from the cold clouds. It follows that in a disc galaxy like the Milky Way a static corona would be rapidly accelerated: the corona is expected to rotate and to lag, in the inner regions, by ~ 80-120 km/s with respect to the cold disc. We also show how the existence of this velocity threshold can explain the observed kinematics of the cold extra-planar gas.